Comparison of K-Nearest Neighbor Algorithm and Logistic Regressionin the Classification of Cervical Cancer Disease - Nur Devita Azzahra; Ambarwati; Anita Desiani; Sri Indra Maiyanti; Indri Ramayanti (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2024)
in the face of the globalization era that is increasingly competitive, a company is required to be able to devise competitive in order to survive and win the competition. Because it needed a solution to improve the quality of the product so that it can assist in winning the competition  with its competitors. PT. Indonesia Timber Kutai (ITC) as a company engaged in lumber and plywood production was should be ableto survive in an increasingly tight competition.Plywood is formed by layers of sheets –sheets of wood called veneer. The quality of the veneers will  effect  the  quality  of  plywood  produced  by  PT  Indonesia  Timber  Kutai.  To  get  a  good  veneer  quality  then needed a good combination between the blade with the machine. Researchers do research on the condition of the blade. A place for pengashan blade is subsi GrindeThe cause of the majority of the knife is a blunt knife quickly, so the quality of the producedveneer  would be ugly. Researchers try to find problems –problems  encountered and  immediately  make  the  effort improved  sharpening  results  with  seven  quality  control.  For  the  results  of  his research  is  before  there  is  an  improvement  obtained  22  case  knife quickly  dulled  from  72  blade,  after  no improvement, found only 1 case of only fast knife dulled from 72 blades